Engaging communities: a primer for landscape architecture practice - Siler, Emily (Kansas State University, 2023)
Recent calls for more democratic design and equitable outcomes have led to a shift within landscape architecture practice towards more meaningful community engagement processes that (1) move beyond conventional, “check-the-box” models, (2) are integrated throughout planning and design processes, and (3) are practiced as an in-house service within landscape architecture firms. Meaningful community engagement processes seek to invite communities into shared dialogue and collaboration to ultimately shape more responsive and relevant planning and design outcomes. As community engagement becomes an increasingly valuable and necessary part of landscape architecture practice, landscape architecture students and emerging professionals could benefit from a “behind the scenes” look at community engagement process—all the thought processes, nuances, important considerations, and detailed decisions that go into a community engagement process. This project aims to build an understanding of how landscape architects develop and implement community engagement processes as a service within their practice. Though there are numerous guides written from a variety of disciplinary backgrounds about how to define, plan, and implement engagement, few are written from a landscape architecture perspective. At the same time, there is a small subset of landscape architecture professionals who have either built a practice around community engagement or have extensive experience leading engagement projects at their firms. Through document analysis of existing community engagement guides and in-depth interviews with experienced landscape architecture professionals, this report connects the dots between what is published in existing guides and what is being practiced in the field. The findings informed a primer on community engagement that includes important considerations for developing engagement processes within landscape architecture practice. The primer is intended to be a resource for landscape architecture students and emerging professionals who not only recognize the importance of community engagement but hope to bring some of this knowledge to their future workplaces.
Keywords: Community engagement; Democratic design; Landscape architecture; Engagement spectrum; Co-create; Equitable outcomes